HeroKeys: Um ambiente virtual gamificado para tocar e aprender piano - Jordão, Deivison R.; Cavalcante, Joaquim B.; Carvalho, Humberto Navarro de; Nunes, Yvson; Gaudencio, Thais; Malheiros, Yuri (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Musical education remains inaccessible to many due to the reliance on traditional methods, which demand sheet music, prior knowledge, or formal training. This paper presents HeroKeys, an open-source gamified web application designed to enhance piano learning through artificial intelligence-based audio transcription. Unlike traditional learning methods that rely on pre-existing transcriptions, HeroKeys allows users to practice any song of their choice by automatically, converting audio files into playable musical notation. The system features multiple visualization options including Piano Roll, traditional sheet music, and a display of the current chord being played, accommodating different learning preferences. The application incorporates gamification elements such as scoring systems, multipliers, and visual feedback to increase user engagement and motivation. HeroKeys supports external MIDI keyboard connections and provides customizable playback controls to facilitate progressive learning. Our approach combines audio processing technologies with interactive elements to create an accessible and motivating piano learning environment, making musical education more engaging and accessible to beginners.